Using the Indocyanine Green (ICG) Lymphography to Screen Breast Cancer Patients at High Risk for Lymphedema - Miao Liu; Siyao Liu; Quanping Zhao; Ying Cui; Jin Chen; Shu Wang (Diagnostics, 2022)
Background: Indocyanine green (ICG) lymphography is a newer technique for diagnosing lymphedema. Our study aimed to find whether the abnormality of ICG lymphography can predict the occurrence of early lymphedema and then select candidates at high risk of developing lymphedema. Methods: Postoperative breast cancer patients who visited the lymphedema clinic of Peking University People’s Hospital from December 2016 to September 2019 were consecutively enrolled and received ICG lymphography and circumference measurement. Data were collected on the patients’ characteristics and correlation between ICG lymphography and the occurrence of lymphedema. Results: The analysis included 179 patients. There were 91 patients in the lymphedema group and 88 patients in the non-lymphedema group. By multivariate analysis, age, axillary surgery, radiotherapy, and time since breast cancer surgery were regarded as risk factors for lymphedema (p < 0.05). According to the results of ICG lymphography, patients in the non-lymphedema group (n = 88) were divided into ICG-positive (n = 47) and ICG-negative (n = 41) groups. The incidence of lymphedema in the ICG-positive group was significantly higher than that in the ICG-negative group (19.1% vs. 2.4%, p = 0.027). Conclusion: Lymphatic disorder can be detected before circumference change using ICG lymphography. Abnormal ICG lymphography is an independent risk factor for lymphedema. Patients with abnormal dermal backflow patterns are considered to be a high-risk group for lymphedema and should undergo early interventions to prevent lymphedema.